Identity construction of Malaysian Indian transgenders - Balan, S. (2014)
This paper investigates the issues of identity construction of life stories of eight adult Indian transgenders who are staying in Malaysia. It aims to examine how trans genders construct their self-identity as to reveal their beliefs and identities according to their life styles through their social discourses. This research helps the readers to think wisely by accepting the transgenders as who they are without need to isolate them because of their genders.